Machinery Hall and Boeing Aerodynamics Chamber viewed from across an ornamental garden, University of Washington campus, approximately 1936
The building on the right is the old Engineering Hall built in 1908 as the Machinery Pavilion for the Alaska Yukon Pacific Exposition. PH Coll 778